The BBNJ negotiations and ecosystem governance in the arctic - De Lucia, Vito (Marine Policy, 2019)
The aim of this article is to explore the question of ecosystem governance in the Arctic, in light of the potential implications of the ongoing negotiations towards a new global treaty on the conservation and sustainable use of marine biodiversity in areas beyond national jurisdiction for ecosystem governance of the Arctic. A new global treaty will have inevitably significant implications for Arctic governance, given that a significant portion of the marine Arctic is located in areas beyond national jurisdiction. The article explores challenges and options for articulating an effective ecosystem approach to marine Arctic biodiversity conservation against the background of diverging negotiating positions on the role of the global treaty in filling governance and regulatory gaps; on the role of regional and sectoral bodies in implementing global rules; on the relationship among them, especially in light of the question of overlapping mandates and competences; as well as in consideration of the work done within the context of the Arctic Council on the ecosystem approach.